What Does the Wavefunction Represent? (Global Journal of Science Frontier Research, 2023)
As was Einstein s original idea we suppose that the speed of light is altered in the presence of mass by a change in its dielectric susceptibility Our explanation of the phenomena of quantum mechanics is a continuation of Einstein search for hidden variables Mass induces a curvature in spacetime This has two effects New volume is created and this would mean that there is not exactly a point particle but matters in a way occupies some volume Another result is that spacetime becomes cyclic and quantities like the action are quantized because they depend on angles through which the observer witnesses the events
Keywords: quantum thermodynamics; hidden variables of quantum mechanics; general relativity